Driving waqf contributions: Understanding alumni behaviour in higher education - Abdul Jabar, Shahira; Ismail, Shafinar; Wan Ismail, Wan Musyirah; Hamzah, Raseeda (Journal of Islamic, Social, Economics and Development, 2026)
A clear understanding of alumni behavioural intention is important for public universities seeking to diversify and strengthen their funding sources, particularly through alumni-based waqf initiatives. This conceptual paper examines the key factors that may influence alumni willingness to contribute to waqf funds in higher education institutions (HEIs) in Malaysia. Public universities are currently facing increasing financial constraints due to reduced government funding and rising operational costs, which highlights the need for sustainable alternative financing mechanisms such as waqf. This study extends the Theory of Planned Behavior (TPB) by contextualising it within Islamic philanthropic behaviour, where waqf is viewed as a spiritually motivated and value-based contribution. In this framework, attitude, social influence, and perceived behavioural control are proposed as key determinants of alumni intention to contribute to educational waqf. By integrating TPB with Islamic social finance perspectives, this paper provides a conceptual understanding of alumni donation behaviour in higher education settings. The proposed framework offers insights for future empirical research and assists higher education institutions in developing more effective alumni engagement strategies to encourage waqf contributions.